EXPLORING CHALLENGES OF TRANSDISCIPLINARY RESEARCH: AN AUSTRALIAN CASE STUDY - Jacques de Vos Malan (European Scientific Journal, ESJ, 2015)
If multidisciplinary research is described as ‘additive’ and interdisciplinary work as ‘interactive’, then a trans-disciplinary project might be best characterized as ‘holistic’. The $10 million Australian research program Securing Australia’s Future (SAF), runs from 2012 to 2016. The aim of the SAF program is to develop evidence-based findings to support public policy-making. The program includes a number of projects that are clearly interdisciplinary in nature. In each case, the research makes use of a conceptual model to link theoretical frameworks from several disciplines. This approach has already been usefully applied across studies as diverse as scientific and cultural diplomacy; economic competitiveness; and shale gas production. One of the latest studies in the SAF program is concerned with sustainable urban mobility. In this case, it might be said that the aim is more than interdisciplinary. The ambition is to develop new conceptual structures beyond discipline-specific views. In other words, the study aims to be transdisciplinary. The paper describes the unfolding plan for delivering such a trans-disciplinary study; identifies critical components of an holistic approach; and proposes methods for evaluating the relative success of the project.